2004
DOI: 10.1038/sj.bdj.4811083
|View full text |Cite
|
Sign up to set email alerts
|

The surface effects of erosion and abrasion on dentine with and without a protective layer

Abstract: Objective The aim of this in situ study was to investigate with four imaging modalities whether covering dentine with adhesive resins could protect against erosion from acids. The objectives were to observe and quantify the effects of acids and the soft tissues, especially the tongue, on dentine and the bonding agents using four assessment techniques: qualitative assessment with SEM, surface roughness and thickness of resin with the TSM and volume loss with the laser profilometer. Design An in situ investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 7 publications
(8 reference statements)
1
57
0
17
Order By: Relevance
“…The application of conventional and self-etching adhesive systems for protection against dentin wear was previously tested, and decreased erosive and abrasive wear was found. 17 The use of adhesives to reduce enamel dissolution after carious acid challenge has also been tested. 18 The adhesives tested in our study were chosen because they are self-etching and do not require prior application of a strong acid for getting retention, which would result in an additional wear on the already eroded surface, thus being more aggressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of conventional and self-etching adhesive systems for protection against dentin wear was previously tested, and decreased erosive and abrasive wear was found. 17 The use of adhesives to reduce enamel dissolution after carious acid challenge has also been tested. 18 The adhesives tested in our study were chosen because they are self-etching and do not require prior application of a strong acid for getting retention, which would result in an additional wear on the already eroded surface, thus being more aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Another study has applied the adhesive over the enamel, and its results showed decreased dissolution of enamel after acid challenge. 18 The treatment of cavity walls with Nd:YAG laser has been investigated to improve the bond strength.…”
Section: 14mentioning
confidence: 99%
“…This method of quantification has been applied for these purposes in different other studies [17,29,30]. For the here used profilometer, a lower limit of measurements of 0.105 µm has been determined, allowing an exact quantification of even the lowest wear (0.82 µm) found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…39 Composite may be placed temporarily or overexposed areas while dentin bonding agents may be effective in reducing sensitivity and preventing further damage. 40 Definitive restorative procedures should not be performed without identification of etiological factors in conjunction with adequate preventive measures.…”
Section: Managementmentioning
confidence: 99%